Antecedents and consequences of servant leadership in local governance: Evidence from three case studies. (5th October 2022) - Awasthi, Pallavi; Walumbwa, Fred O.
Abstract: Although servant leadership has emerged as an important community‐oriented leadership approach that is desirable for public organizations, relatively less research attention has been devoted to understanding its antecedents as well as its organizational and community‐level consequences. Drawing on self‐categorization and stakeholder theories, this study investigates the antecedents and consequences of servant leadership in local government agencies using a comparative analysis of three case studies (two counties and a city). Findings highlight two frameworks of antecedents and consequences of servant leadership in local governance: (1) the underlying mechanisms—translating antecedents into servant leadership and (2) the intervening mechanisms—translating as organizational and community‐level consequences of servant leadership. These findings have implications for both public sector leadership theory and practice. Theoretically, servant leadership emerges as an inclusive approach that fosters stakeholder engagement and community prosperity in local governments. Practically, the findings suggest a pathway for utilizing servant leadership as an instrument for potential selection, training, succession planning, and servant leadership development in local government managers.